2020
DOI: 10.1097/dss.0000000000002646
|View full text |Cite
|
Sign up to set email alerts
|

Aging Changes of the Superficial Fat Compartments of the Midface Over Time: A Magnetic Resonance Imaging Study

Abstract: BACKGROUND Studies involving superficial facial fat compartments are few in number with conflicting results. Most of them involved small study groups and compared measurements between different populations of young and old subjects either on cadavers or living subjects. OBJECTIVE To clarify volumetric and dimensional changes in midfacial superficial fat compartment retrospectively in patients who underwent a repeat magnetic resonance imaging (MRI) witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…The height was also found to increase significantly. The width increased in the lower compartment while the upper and lower compartments narrowed down with age 9 . Similarly, the present study found a decrease in volume and thickness in the upper and middle compartments, an increase in width in the lower compartment, and an increase in height.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The height was also found to increase significantly. The width increased in the lower compartment while the upper and lower compartments narrowed down with age 9 . Similarly, the present study found a decrease in volume and thickness in the upper and middle compartments, an increase in width in the lower compartment, and an increase in height.…”
Section: Discussionsupporting
confidence: 84%
“…The width increased in the lower compartment while the upper and lower compartments narrowed down with age. 9 Similarly, the present study found a decrease in volume and thickness in the upper and middle compartments, an increase in width in the lower compartment, and an increase in height. The discrepancies between the results of the two studies can be explained by the number of patients (n = 70 and n = 262, respectively), the average age of the patients (60 and 46 years, respectively), and the interval between the two imagings (44.5 and 56 months, respectively).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Aging also results in a deficiency of facial fat compartments (Cenkeri et al, 2020), which can easily be reversed with fat injections (Obagi and Willis, 2018) or facial fillers (Philipp-Dormston et al, 2020). On the other hand, neither fillers nor the energy-based devices cannot be used successfully to lift the descended parts of the face; however, they are great adjuncts following facelift to obtain a better aesthetic outcome (Hammoudeh and Stevens, 2019).…”
Section: Introductionmentioning
confidence: 99%